Effect of Marital Status on Upper Digestive Tract Tumor Survival: Married Male Patients Exhibited a Better Prognosis - Qing, Maofeng; Peng, Jiakuan; Shang, Qianhui; Xu, Hao; Chen, Qianming (Frontiers in Surgery, 2022)
Purpose: Marital status has been associated with outcomes in several cancers, but little is known about upper digestive tract tumors (UDTT). The study aims to explore the effect of marital status on survival outcomes of UDTT. Methods: We collected patient cases of UDTT using the Surveillance, Epidemiology and End Results (SEER) database between 1975 and 2016. Univariate analyses of overall survival (OS) and cancer-specific survival (CSS) were performed using the Kaplan-Meier method. Multivariate survival analyses were performed by Cox proportional hazard model. Results: A total of 282,189 patients were included, with 56.42%, 16.30%, 13.33%, and 13.95% of patients married, never married, divorced/separated and widowed, respectively. Significant differences were observed among married, never married, divorced/separated and widowed patients with regard to the year of diagnosis, sex, age, race, pathological type, anatomical site, number of primary tumor, grade, rate of surgery performed, radiotherapy, chemotherapy (P<0.001). The proportions of patients with 3-year and 5-year OS were 54.22% and 48.02% in the married group, 46.96% and 41.12% in the never married group, 44.24% and 38.06% in the divorced/separated group, 34.59% and 27.57% in the widowed group, respectively (P<0.001); the proportions of patients with 3-year and 5-year CSS were 70.76% and 68.13% in the married group, 62.44% and 59,93% in the never married group, 63.13% and 60.53% in the divorced/separated group, 62.11% and 58.89% in the widowed group respectively (P<0.001); all these data indicated married patients exhibited favorable OS and CSS than never married, divorced/separated and widowed patients. Men in the married group showed better OS (HR, 1.16; 95%CI 1.11-1.22) and CSS (HR, 0.96; 95%CI 0.92-1.23) than those in the never married group. Conclusion: The study reveals that marital status is an independent prognostic factor for OS and CSS of patients with UDTT. Married male patients with UDTT trend to have a better prognosis.